The potential of lemon juice-ogi steep liquor mixtures in the reduction of Listeria monocytogenes contamination of ready-to-eat vegetables. (December 2016) - Ajayeoba, Titilayo; Atanda, Olusegun; Obadina, Adewale; Bankole, Mobolaji; Brumbley, Steven
Abstract: This study evaluated the inhibitory effect of lemon juice ogi steep liquor mixtures (10–50% v/v) made from white and yellow maize, white and red sorghum and Pearl millet grains on three antibiotic resistant isolates (LM 29, 33 and 44) and a susceptible isolate (LM 50) of Listeria monocytogenes. The isolates were surface-inoculated onto ready-to eat-vegetables (cucumber- Cucumis sativas, cabbage- Brassica olerecea, carrot- Daucus carota, tomato- Solanum lycopersicum, lettuce -Lactuca sativa) . The most effective concentration (50% v/v, lemon juice-white sorghum) of the mixtures was further used for bioassay of vegetables contaminated with isolate with the lowest zone of inhibition (LM 29) to the treatments at dipping times of 0–20 min. The major active compounds in the mixtures were also elucidated with Fourier Transform Infra-Red spectroscopy. There were significant differences (p ≤ 0.05) in the responses of the isolates to the treatments which varied with types of isolates, the cereal sources and contact times. There were reductions in the colonies of the isolates as the dip time increased and the isolates inoculated onto carrots; cucumbers and lettuce were completely inhibited at 10, 15 and 20 min treatment times. Alcohol and carboxylic acids were identified as the major active compounds responsible for reduction and inhibition of the isolates. Highlight: Lemon juice-white sorghum steep liquor at 50:50 (v/v) was most effective in reduction of Listeria monocytogenes contamination of RTE vegetables.